The Role of Liberal Arts Education on Academic Choices: The American University in Cairo Case Study - El Maraghi, Nourhane Mohamed Kamal (AUC Knowledge Fountain, 2022)
Providing a qualified higher education is a crucial component of any developmental plan in any country. This paper tackles the issue of educational decisions and will mainly focus on presenting the American University in Cairo (AUC) as a case study. The paper addresses undergraduate college students’ choices of their subjects and fields of study during the first year of university and how liberal arts education influence such decisions. The main aim is to build valuable recommendations to ease the transition of students from high school to universities, help them rationally choose their area of study, facilitate the financial burden on students and their families, eliminate discrimination among students, and highlight the importance of inclusivity of various types of students in the academic institutions to have well-rounded candidates who serve the developmental plans of their country. The research proves the close relationship between the previously mentioned factors and students’ academic decisions. Using the liberal arts concepts while updating curriculums and policies may benefit students. Realize career plans and have compatible jobs. Assessing and improving the relevance of the Egyptian higher education system could be one of the leading forces behind the country’s development and growth.